Предмет:
АлгебраАвтор:
valerianocannonАвтор:
patelАвтор:
nelsonmrt8a) y(a - b) - 3(a - b)
(a - b) (y - 3)
Автор:
lady7kaaA) =(a-b)(y-3)
b) 3x^2 -x^2+12x-4=0
2x^2+12x-4=0
2 (x^2+6x-2)=0
x^2+6x-2=0
D=b^2-4ac=36+8=44
X(1) =( -6 - √44) / 2 = (-6 - 2√11) / 2 = 2(-3 - √11)/2 = -3 - √11
x(2) = (-6 + 2√11 )/ 2 = 2(-3 +√11) / 2 = -3 +√11 = √11 - 3
Автор:
joycealiДобавить свой ответ
Предмет:
Русский языкАвтор:
sundayОтветов:
Смотреть
Предмет:
МатематикаАвтор:
justineОтветов:
Смотреть
Предмет:
МатематикаАвтор:
pierce74Ответов:
Смотреть
Предмет:
МатематикаАвтор:
billiejenkinsОтветов:
Смотреть